Devices for In situ Development of Non-disturbed Oral Biofilm. A Systematic Review - Prada-López, Isabel; Quintas, Víctor; Vilaboa, Carlos; Suárez-Quintanilla, David; Tomás, Inmaculada (Frontiers in Microbiology, 2016)
Objective: The aim of this review was to assess the types of devices used for in situ development of oral biofilm analysed microbiologically. Material and Methods: A systematic search of the literature was conducted to identify all in situ studies of oral biofilm which used an oral device; the Ovid MEDLINE and EMBASE databases complemented with manual search were used. Specific devices used to microbiologically analyse oral biofilm in adults were included. After reading of the selected full texts, devices were identified and classified according to the oral cavity zone and manufacturing material. The “ideal” characteristics were analysed in every group. Results: The search provided 787 abstracts, of which 112 papers were included. The devices used in these studies were classified as palatal, lingual or buccal. The last group was sub-classified in six groups based on the material of the device. Considering the analysed characteristics, the thermoplastic devices and the Intraoral Device of Overlaid Disk-holding Splints (IDODS) presented more advantages than limitations. Conclusions: Buccal devices were most commonly used for the study of in situ biofilm. The majority of buccal devices seemed to slightly affect the volunteer’s comfort, the IDODS being the closest to the “ideal” model. Clinical Relevance: New devices for in situ oral biofilm microbiological studies should take into account the possible effect of their design on the volunteer’s comfort and biofilm formation.